A Systematic Literature Review of Psychosocial and Behavioral Factors Associated with Initial Medication Adherence: A Report of the ISPOR Medication Adherence & Persistence Special Interest Group - Zeber, John E.; Manias, Elizabeth; Williams, Allison F.; Hutchins, David; Udezi, Waka A.; Roberts, Craig S.; Peterson, Andrew M. (Value in health, 2013)
Numerous factors influencing medication adherence in chronically ill patients are well documented, but the paucity of studies concerning initial treatment course experiences represents a significant knowledge gap. As interventions targeting this crucial first phase can affect long-term adherence and outcomes, an international panel conducted a systematic literature review targeting behavioral or psychosocial risk factors. Eligible published articles presenting primary data from 1966 to 2011 were abstracted by independent reviewers through a validated quality instrument, documenting terminology, methodological approaches, and factors associated with initial adherence problems. We identified 865 potentially relevant publications; on full review, 24 met eligibility criteria. The mean Nichol quality score was 47.2 (range 19–74), with excellent reviewer concordance (0.966, P < 0.01). The most prevalent pharmacotherapy terminology was initial, primary, or first-fill adherence. Articles described the following factors commonly associated with initial nonadherence: patient characteristics (n = 16), medication class (n = 12), physical comorbidities (n = 12), pharmacy co-payments or medication costs (n = 12), health beliefs and provider communication (n = 5), and other issues. Few studies reported health system factors, such as pharmacy information, prescribing provider licensure, or nonpatient dynamics. Several methodological challenges synthesizing the findings were observed. Despite implications for continued medication adherence and clinical outcomes, relatively few articles directly examined issues associated with initial adherence. Notwithstanding this lack of information, many observed factors associated with nonadherence are amenable to potential interventions, establishing a solid foundation for appropriate ongoing behaviors. Besides clarifying definitions and methodology, future research should continue investigating initial prescriptions, treatment barriers, and organizational efforts to promote better long-term adherence.